Revised annotation of Plutella xylostella microRNAs and their genome‐wide target identification. Issue 6 (12th August 2016) - Etebari, K.; Asgari, S.
Abstract: The diamondback moth, Plutella xylostella, is the most devastating pest of brassica crops worldwide. Although 128 mature microRNAs (miRNAs) have been annotated from this species in miRBase, there is a need to extend and correct the current P. xylostella miRNA repertoire as a result of its recently improved genome assembly and more available small RNA sequence data. We used our new ultra‐deep sequence data and bioinformatics to re‐annotate the P. xylostella genome for high confidence miRNAs with the correct 5p and 3p arm features. Furthermore, all the P. xylostella annotated genes were also screened to identify potential miRNA binding sites using three target‐predicting algorithms. In total, 203 mature miRNAs were annotated, including 33 novel miRNAs. We identified 7691 highly confident binding sites for 160 pxy‐miRNAs. The data provided here will facilitate future studies involving functional analyses of P. xylostella miRNAs as a platform to introduce novel approaches for sustainable management of this destructive pest.